EVALUASI PROGRAM PENDIDIKAN KARAKTER BERBASIS BUDAYA SEKOLAH (STUDI KASUS DI SMP NEGERI 8 AMBON) - Adha Marche Lino Untajana; Sally Edoxiana Untajana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study evaluates the implementation of character education at SMP Negeri 8 Ambon, Indonesia, using the Goal-Free Evaluation model to identify actual outcomes beyond predefined objectives. Character education, integrated into daily school culture as "habituation activities," aims to foster values such as religiosity, honesty, and discipline. Employing a qualitative descriptive approach, data were collected via interviews with school leaders, teachers, staff, and students, alongside participant observation and document analysis. Findings reveal that habituation practices—daily flag ceremonies, prayers, national song singing, 5S (smile, greet, salute, be polite and gentle), and cleanliness routines—have successfully become embedded in school culture, involving all stakeholders. This integration has yielded significant positive outcomes: improved student discipline (reduced tardiness), enhanced school cleanliness, stronger teacher-student relationships, increased participation in cultural competitions, and a more respectful school environment. Key success factors include consistent role modeling by staff and leadership, adequate infrastructure (e.g., trash bins, prayer rooms), and community support. Challenges include residual misconceptions among some staff who view character education as solely the responsibility of specific subjects. The study concludes that embedding character education within daily school routines, grounded in consistent modeling and institutional support, is highly effective in cultivating student character.